Thyroid cancer in West Java: It’s not all papillary and pretty - Rizki, Kiki Akhmad; Kurniasari, Rantapina; Priosadewo, Monty; Abdurrahman, Maman; Azhar, Raden Yohana; Gaol, Dodi Lumban; Sitanggang, Rupita Sari Endangena; Erdiansyah, Zuldi; Nugraha, Prapanca; Muhammad, Arrayyan; Primastari, Etis (Cancer epidemiology, 2025)
Thyroid cancer is the most common endocrine malignancy in children and adults. The rising incidence of thyroid cancer, which remains poorly understood, raises the need to evaluate whether this increase will lead to higher mortality and more aggressive disease. This study aimed to describe the characteristics of thyroid cancer at the largest hospital in West Java and to examine the relationships between these characteristics. This was an observational study. The subjects were patients with thyroid tumors in the oncology surgery division of a tertiary hospital in West Java, Indonesia, from January 2017 to December 2022. A total of 3414 subjects were included in the study. The characteristics of the thyroid tumors were extracted from medical records. The results showed that the mean age of the participants was 47 years, thyroid tumors were more common in women (82.9 %), and tumor location was frequently found on the right side (38.6 %) and over 90 % of cases showed no lymph node metastasis. Univariate analysis confirmed significant associations between histology and patient sex, tumor location, size, and nodal status (all p < 0.05), with very few subcentimeter tumors and higher metastatic rates in papillary (30.3 %) and medullary (37.5 %) carcinomas. Thyroid cancer, particularly papillary thyroid carcinoma, was prevalent in the study population, with significant associations between histopathology, sex, tumor size, and lymph node metastasis. These findings highlight the important of using risk-based FNA and selective surgical referral to exclude low-risk microcarcinomas. Adherence to these strategies will mitigate overdiagnosis and unnecessary surgery. •Large-scale study of 3414 thyroid cases in West Java, Indonesia.•Detailed analysis of demographic and clinical patterns in thyroid disorders.•Significant links observed between tumor subtype and sex, size, and metastasis.•Novel insights to refine early detection and management of thyroid cancers.